Fluid-structure interactions in Low-Reynolds-number flows - Duprat, Camille; Stone, Howard A. (Professor of Mechanical and Aerospace Engineering) (RSC soft matter series, 2015)
Fluid-structure interactions have been well studied over the years but most of the focus has been on high Reynolds number flows, inertially dominated flows where the drag force from the fluid typically varies as the square of the local fluid speed. There are though a large number of fluid-structure interaction problems at low values of the Reynolds number, where the fluid effects are dominated by viscosity and the drag force from the fluid typically varies linearly with the local fluid speed, which are applicable to many current research areas including hydrodynamics, microfluidics and hemodynamics. Edited by experts in complex fluids, Fluid-Structure Interactions in Low-Reynolds-Number Flows is the first book to bring together topics on this subject including elasticity of beams, flow in tubes, mechanical instabilities induced by complex liquids drying, blood flow, theoretical models for low-Reynolds number locomotion and capsules in flow. The book includes introductory chapters highlighting important background ideas about low Reynolds number flows and elasticity to make the subject matter more approachable to those new to the area across engineering, physics, chemistry and biology.